Diseño de un sistema de costos por actividades (abc) en el área de la cocina del complejo turístico “Agua Luna”, ubicado en el cantón Latacunga sector la Calera del periodo 2022. - Choloquinga Ayala, Jessica Elizabeth (2023)
This project aims to address the proposal of a cost system within tourism activity, which is considered one of the most relevant activities in recent times for which the objective was to design a cost system by activities (ABC) in the kitchen area of “Agua Luna" Tourist Complex, located in Latacunga Canton, La Calera sector for 2022 period, parameterized to "Agua Luna" tourist complex, in order to analyze the costs incurred in the elaboration. The entity subject to study presents as absence problematic of an efficient costing control by managing elaboration through observation and not with documented records that offer a correct organization, offering its gastronomic products based on that structure; it does not have a sequential order at production since they are carried out simultaneously, that, they are prepared at the same time thanks to the personnel. Therefore, the design was developed through gastronomic dishes made according to their costs and time. The used methodology in the research has a quantitative, descriptive, analytical approach developed through analysis by numerical values to harmonize management and performed activities, allowing to know economic environment of tourist complex. Thanks to implementation system, an efficient calculation was observed, in which differences are found framed in a lower cost calculated by ABC costing system compared to traditional costing, allow to know and identify incurred costs in production, taking into consideration the cost of each dish as it generates a variation in favor of the business of: 0.25 equals -2. 81% in the complete barbecue "aguluna", in the second 0.10 which is equivalent to -1.29% in the ½ barbecue "agualuna", and in the third dish 0.37 which is equivalent to 4.51% in the ½ barbecue "aguluna" special, as well as the use of control documents that manage inventories. In conclusion, the proposed model will allow optimiz its processes and cost control, developing efficiency in production and serving as a tool for decision making.